2019
DOI: 10.1590/1809-4430-eng.agric.v39n3p280-287/2019
|View full text |Cite
|
Sign up to set email alerts
|

Bed Temperature in Compost Barns Turned With Rotary Hoe and Offset Disc Harrow

Abstract: The success of confinement for dairy cattle in the compost barn model depends mainly on the management of the bed and consists of its turning. This paper characterises the spatial variability of the bed temperature in the compost barn confinement model, as well as verifying whether there was an effect on efficiency from turning the bed with different agricultural implements. The experiment was conducted during the summer and winter of 2016, with 8 days of collection in each period. Data were analysed with desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
2
1
0
1
Order By: Relevance
“…In the current study, the constructive aspect of the barn also contributed to the heating of the bed at borders of the rest area. Similar findings were reported by Mota et al, 2019. The dimensioning of the eaves allowed the direct entry of solar radiation more intensely during morning shift, this result which may explain BST coefficients of variation values (CV >15%).…”
Section: Arqsupporting
confidence: 87%
See 2 more Smart Citations
“…In the current study, the constructive aspect of the barn also contributed to the heating of the bed at borders of the rest area. Similar findings were reported by Mota et al, 2019. The dimensioning of the eaves allowed the direct entry of solar radiation more intensely during morning shift, this result which may explain BST coefficients of variation values (CV >15%).…”
Section: Arqsupporting
confidence: 87%
“…However, as it is a process in which the bedding composes a material that undergoes partial composting (Russelle et al, 2009), reaching optimum temperatures becomes a challenge for milk producers. Following this fact, research using Compost barn in Brazil, including the present work, reported systems in which the ideal temperature range was not reached (Mota et al, 2019;Piovesan and Oliveira, 2020).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Analisar e estudar a variabilidade espacial do microclima das baias para equinos é essencial para corrigir falhas na estrutura física e para controlar as condições de bem-estar e saúde do animal (FARIA et al, 2008;SILVA et al, 2012, MOTA et al, 2019. Diante do exposto, o objetivo deste trabalho é avaliar a distribuição espacial da temperatura do ar no interior de baías de equinos, de uma propriedade rural do município de Ji-Paraná/RO, bem como utilizar a modelagem geoestatística para mapear e analisar se a estrutura fornece conforto e bem-estar aos animais.…”
Section: Introductionunclassified